[EN] Characteristics of Classical Arabic Literary Prose (Afaq Lughawiyyah, 2024)
One aspect of literature that is highly sought after by many people is imaginative or creative literature. Two major components of creative literature are poetry and prose, each possessing various characteristics that can captivate the attention of enthusiasts. The Arab country stands out as one of the nations with an exceptionally rich literary culture. The produced prose is highly diverse and carries extraordinary messages and embellishments, imbuing it with significant value. Therefore, this article will encompass the characteristics of classical Arabic literary prose. The method employed in this study is the library research method, which involves collecting data relevant to the topics discussed in this article and presenting it in a descriptive form. The findings reveal that the concept of prose in the Arab world exhibits unique traditions and characteristics that set it apart from other forms of prose. The characteristics of Arabic prose, which originated from the Jahiliyah period in the form of al-khitab, al-wasaya, and al-hikam, continue to evolve to this day. As for the general characteristics that can be found in classical Arab literary prose, among them are eloquence and rhetoric, rich vocabulary, imagery and descriptive language, poetic elements, complex sentence structure, themes of honor and morality, storytelling tradition, cultural and historical context, Islamic influence.